Investigation of the Light Intensity Effect on Growth, Molting, Hemolymph Lipid, and Antioxidant Capacity of Juvenile Swimming Crab Portunus trituberculatus - Xu, Hanying; Dou, Juan; Wu, Qingyang; Ye, Yangfang; Song, Changbin; Mu, Changkao; Wang, Chunlin; Ren, Zhiming; Shi, Ce (Frontiers in Marine Science, 2022)
An eight-week experiment was conducted to evaluate the effects of eight light intensities (0, 0.83, 1.61, 8.17, 15.89, 31.38, 63.69, and 124.31 μmol m-2 s-1) on the survival, growth, antioxidant, molting-related and apoptosis-related gene expression of juvenile swimming crab Portunus trituberculatus. The results showed that the survival rate of crabs was the highest under the light intensities of 8.17 and 15.89 μmol m-2 s-1. Under this light intensity, the crabs had the lowest hemolymph glucose (GLU) but the highest triglyceride (TG) content. The crabs in these treatments also had the highest total antioxidant capacity (T-AOC), superoxide dismutase (SOD), catalase (CAT) activities, and the lowest malondialdehyde (MDA) content. The growth performance (including weight gain and specific growth rate) and molting frequency of crabs increased with increasing light intensity. The improved growth performance and molting of 8.17 and 15.89 μmol m-2 s-1 groups were also accompanied by up-regulated of the retinoid-X receptor (rxr), ecdysone receptor (ecr), nuclear receptor E75 (e75) gene expression, and down-regulated molt-inhibiting hormone (mih) gene expression. In addition, suboptimal light intensity (0, 0.83, 63.69, and 124.31 μmol m-2 s-1) significantly up-regulated the expression of apoptosis-related genes including c-Jun N-terminal kinase (jnk), tumor suppressor p53 (p53), and B-cell lymphoma-2 (bcl-2). Taken together, the suitable light intensity for the juvenile P. trituberculatus was estimated to be 9.96 μmol m-2 s-1.